Eleventh hour CISSP : study guide - Conrad, Eric, 1967- (Syngress eleventh hour series., 2011)
The Eleventh Hour CISSP Study Guide is keyed to the latest CISSP exam. This book is streamlined to include only core certification information and is presented for ease of last-minute studying. Main objectives of the exam are covered concisely with key concepts highlighted. The only guide you need for last-minute studying. Answers the toughest questions and highlights core topics. Can be paired with any other study guide so you are completely prepared.